AI in Accounting and Finance: A Literature Review on Challenges, Opportunities, and Ethical Considerations - Oktaria Simatupang (International Journal of Information System and Innovative Technology, 2024)
The integration of Artificial Intelligence (AI) in accounting and finance has significantly transformed traditional practices by enhancing efficiency, accuracy, and decision-making. This paper presents a structured literature review exploring the opportunities AI provides, including automation, data analysis, and fraud detection, while also discussing challenges such as transparency, data security, and ethical concerns. A comparative analysis of existing research highlights the key differences in AI adoption across industries and organizations. The study also identifies research gaps, particularly in ethical AI implementation, workforce transformation, and AI adoption among small and medium-sized enterprises (SMEs). By addressing these gaps, the paper contributes to a better understanding of how AI can be responsibly integrated into accounting and